EFEKTIVITAS LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK MODELLING UNTUK MENINGKATKAN SELF-EFFICACY SISWA KELAS VIII SMP NEGERI 2 SAKETI TAHUN AJARAN 2024/2025 - Resti Rahayu; Muhamad Ikhsan; Fitri Arnita (Afeksi: Jurnal Psikologi, 2024)
This study aims to determine the effectiveness of group counseling services using modeling techniques to enhance students' self-efficacy. The research employs a quantitative method with a quasi-experimental design. Specifically, the study adopts a Non-equivalent Control Group Design. The population consists of 75 eighth-grade students at SMP Negeri 2 Saketi, with a sample of 28 students divided into two groups: an experimental group and a control group, each consisting of 14 students. Data were collected using a self-efficacy scale developed by the researcher, which was validated through expert judgment. Data analysis involved normality testing, homogeneity testing, and t-tests. The results revealed a significant difference in the pretest and posttest scores after the intervention. The hypothesis testing, using the t-test, showed an Asymp. Sig (2-tailed) value of 0.000, which is less than 0.05. This indicates that the group counseling intervention using modeling techniques was effective in enhancing students' self-efficacy. Therefore, it can be concluded that group counseling services with modeling techniques are effective in improving self-efficacy among eighth-grade students at SMP Negeri 2 Saketi during the 2024/2025 academic year.